IRON DEFICIENCY ANEMIA AND CURRENT STATE OF KNOWLEDGE AMONG ADOLESCENT GIRLS, LAMPUNG-INDONESIA - Nurhayati Nurhayati; Agni Laili Perdani; Eka Trismiyana (Malahayati International Journal of Nursing and Health Science, 2019)
Background: Anemia is a condition with lower hemoglobin and hematocrit levels. The number of iron deficiency in Indonesia among children aged 5 to 14 years is still quite high at 26.4%. Less knowledge in adolescent caused by the consumption of unhealthy food or light snacks.Purpose: To describe the relationship of  Iron deficiency anemia and  current state of knowledge among adolescent girls in 1st Mesuji Junior High School.Methods: The type of this research is an observational study with a cross-sectional method. The population of this study was members of all adolescent girls in class VIII and IX at 1st Mesuji Junior High School with the total is 87 respondents. Data collected by a questionnaire and analyzed used chi-square.Results: The most of the respondents 47 (54%) had poor knowledge about Iron deficiency anemia and experienced of Iron deficiency anemia 44 (50.6%) with p-value = 0.001.  Conclusion: There is a relationship between Iron deficiency anemia and  current state of knowledge among adolescent girls, Mesuji Junior High School in 2018.  It is recommended for school management to further improve health promotion or counseling about Iron deficiency anemia in adolescent girls, especially in prevention.